2020
DOI: 10.2147/idr.s252485
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antimicrobial Susceptibility of <em>Mycobacterium abscessus</em> Complex Clinical Isolates from a Chinese Tertiary Hospital</p>

Abstract: Introduction: Mycobacterium abscessus complex (MABC) is a group of important infectious agents that are highly associated with drug resistance, and antibiotic treatment is usually ineffective. This study investigated the characteristics of antimicrobial susceptibility of MABC isolates and the synergy between certain β-lactam combinations against MABC infection. Methods: We collected 129 MABC isolates from patients with lower respiratory tract infections and categorized them into three subspecies. The minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
4
6
1
1
Order By: Relevance
“…The earliest studies of β-lactam antibiotics indicated little antitubercular activity. It was soon recognized that their apparent inactivity was due to the presence of mycobacterial β-lactamases . Penicillinase-resistant penicillins, such as oxacillin, and third-generation cephalosporins, which are poor substrates for the mycobacterial β-lactamase, were observed to possess activity. , Later it was demonstrated that carbapenems and combinations of β-lactam antibiotics and β-lactamase inhibitors were also active antimycobacterial agents. The major Mtb β-lactamase, BlaC, is an endogenous Ambler class A serine penicillinase that has broad substrate specificity and is inhibited by clavulanic acid. A combination of clavulanic acid and the carbapenem meropenem was shown to be active against XDR- Mtb and recent studies compared in vitro efficacy of several β-lactam/β-lactamase inhibitor combinations against MDR-TB. Mab also expresses an endogenous serine class A β-lactamase, Bla Mab , with broad substrate specificity that hydrolyzes the conventional β-lactamase inhibitors, clavulanate, sulbactam, and tazobactam, but is inhibited by the newer diazabicyclooctanes (DBO, e.g., avibactam, relebactam) and boronic acid (e.g., vaborbactam) inhibitors. Carbapenems were found to be more effective against Mab in combination with other antibiotics, both β-lactam and non-β-lactam, rather than when used alone. Newly designed penems are in development to treat Mab …”
mentioning
confidence: 99%
“…The earliest studies of β-lactam antibiotics indicated little antitubercular activity. It was soon recognized that their apparent inactivity was due to the presence of mycobacterial β-lactamases . Penicillinase-resistant penicillins, such as oxacillin, and third-generation cephalosporins, which are poor substrates for the mycobacterial β-lactamase, were observed to possess activity. , Later it was demonstrated that carbapenems and combinations of β-lactam antibiotics and β-lactamase inhibitors were also active antimycobacterial agents. The major Mtb β-lactamase, BlaC, is an endogenous Ambler class A serine penicillinase that has broad substrate specificity and is inhibited by clavulanic acid. A combination of clavulanic acid and the carbapenem meropenem was shown to be active against XDR- Mtb and recent studies compared in vitro efficacy of several β-lactam/β-lactamase inhibitor combinations against MDR-TB. Mab also expresses an endogenous serine class A β-lactamase, Bla Mab , with broad substrate specificity that hydrolyzes the conventional β-lactamase inhibitors, clavulanate, sulbactam, and tazobactam, but is inhibited by the newer diazabicyclooctanes (DBO, e.g., avibactam, relebactam) and boronic acid (e.g., vaborbactam) inhibitors. Carbapenems were found to be more effective against Mab in combination with other antibiotics, both β-lactam and non-β-lactam, rather than when used alone. Newly designed penems are in development to treat Mab …”
mentioning
confidence: 99%
“…This rate was significantly higher than those from the USA (4.8%), 15 South Korea (3.4%), 16 France (4.8%), 17 and Shanghai (3.9%). 18 Several potential explanations could be responsible for the high AMK resistance rate observed in our study. On the one hand, there was a great range in the literature regarding the drug susceptibilities of MAB and M. massiliense .…”
Section: Discussionmentioning
confidence: 86%
“…A recent study by Guo and colleagues demonstrated that the rate of AMK resistance for MAB (4.1%) was dramatically higher than that for M. massiliense in Shanghai (0.0%). 18 In contrast, a systematic analysis of a global genome dataset found that a slightly higher proportion of M. massiliense genomes contained the canonical rrs mutation conferring high-level AMK resistance than MAB. 19 Hence, we speculate that the diverse results across studies may be due to the differences in subspecies compositions.…”
Section: Discussionmentioning
confidence: 94%
“…The first two subspecies have functional erm(41) genes, while the massiliense subspecies has no functional erm(41) genes and remain macrolide susceptible at the first macrolide treatment [ 13 ]. Induced resistance to macrolides in MAB was reported to be 68.4% and 74.3% for the abscessus and bolletii subspecies, respectively, while no induced resistance was found in the massiliense subspecies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%